The PDZ Protein GIPC Regulates Trafficking of the LPA1 Receptor from APPL Signaling Endosomes and Attenuates the Cell’s Response to LPA - Varsano, Tal; Taupin, Vanessa; Guo, Lixia; Baterina, Oscar Y., Jr; Farquhar, Marilyn G. (PLOS ONE, 2012)
Lysophosphatidic acid (LPA) mediates diverse cellular responses through the activation of at least six LPA receptors – LPA1–6, but the interacting proteins and signaling pathways that mediate the specificity of these receptors are largely unknown. We noticed that LPA1 contains a PDZ binding motif (SVV) identical to that present in two other proteins that interact with the PDZ protein GIPC. GIPC is involved in endocytic trafficking of several receptors including TrkA, VEGFR2, lutropin and dopamine D2 receptors. Here we show that GIPC binds directly to the PDZ binding motif of LPA1 but not that of other LPA receptors. LPA1 colocalizes and coimmunoprecipitates with GIPC and its binding partner APPL, an activator of Akt signaling found on APPL signaling endosomes. GIPC depletion by siRNA disturbed trafficking of LPA1 to EEA1 early endosomes and promoted LPA1 mediated Akt signaling, cell proliferation, and cell motility. We propose that GIPC binds LPA1 and promotes its trafficking from APPL-containing signaling endosomes to EEA1 early endosomes and thus attenuates LPA-mediated Akt signaling from APPL endosomes.